Zambia: Recent developments in agricultural research - Flaherty, Kathleen; Mwala, Mick S. (International Food Policy Research Institute, 2010)
After three decades of fluctuating but overall diminishing public agricultural research and development (R&D) spending in Zambia, the downward trend of investment accelerated during 2001-08. In 2008, Zambia spent 20 billion kwacha or 8 million PPP dollars on public agricultural R&D, both in 2005 constant prices, compared with 24 billion kwacha or about 10 million PPP dollars in 2001, and 89 billion kwacha or 37 million PPP in 1991. Unless otherwise stated, all dollar values in this note are expressed in purchasing power parity (PPP) prices. PPPs reflect the purchasing power of currencies more effectively than do standard exchange rates because they compare the prices of a broader range of local-as opposed to internationally traded-goods and services. Public agricultural R&D capacity increased in the 1980s, then experienced a sharp decline in the early 1990s. A period of growth in the mid-1990s was then followed by another period of contraction, up through 2006, primarily due to a government-sector hiring freeze imposed from 2002 until 2007. When recruitment resumed, research capacity grew quickly and returned to mid-1990s levels by 2008, with a total of 209 full-time equivalent (FTE) research staff employed that year.